2018
DOI: 10.3390/ijms20010059
|View full text |Cite
|
Sign up to set email alerts
|

We Are What We Eat: A Stoichiometric and Ecometabolomic Study of Caterpillars Feeding on Two Pine Subspecies of Pinus sylvestris

Abstract: Many studies have addressed several plant-insect interaction topics at nutritional, molecular, physiological, and evolutionary levels. However, it is still unknown how flexible the metabolism and the nutritional content of specialist insect herbivores feeding on different closely related plants can be. We performed elemental, stoichiometric, and metabolomics analyses on leaves of two coexisting Pinus sylvestris subspecies and on their main insect herbivore; the caterpillar of the processionary moth (Thaumetopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Thus, understanding plant species' metabolic shifts in response to drought will allow prediction and mitigation of ecological change in wild and crop plant communities under scenarios of increased drought. In addition, changes in plant metabolome may affect community composition and ecosystem trophic webs through shifts in the nutritional value of plant tissues or through the accumulation of secondary protective compounds that may play a role as attractants/repellents, triggered by acclimation mechanisms to environmental change [2,5,21]. Gaining a deeper understanding of metabolic adaptive strategies to short-term drought effects may thus be useful in the selection of novel drought-resistant genotypes of crop plant species.…”
Section: Droughtmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, understanding plant species' metabolic shifts in response to drought will allow prediction and mitigation of ecological change in wild and crop plant communities under scenarios of increased drought. In addition, changes in plant metabolome may affect community composition and ecosystem trophic webs through shifts in the nutritional value of plant tissues or through the accumulation of secondary protective compounds that may play a role as attractants/repellents, triggered by acclimation mechanisms to environmental change [2,5,21]. Gaining a deeper understanding of metabolic adaptive strategies to short-term drought effects may thus be useful in the selection of novel drought-resistant genotypes of crop plant species.…”
Section: Droughtmentioning
confidence: 99%
“…The term "ecometabolomics", which first appeared in the scientific literature in 2009 [1,2], describes the use of nontarget metabolomics to study the responses, acclimation and adaptation of living organisms to environmental conditions [3][4][5][6]. The advances in nontarget analytical platforms has provided a new tool for ecologists and environmental researchers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel chemical characterization methods, such as MS-based metabolomics, can produce a large number of markers (metabolomic features) that can be used to identify more precisely low-concentration PBAPs present in the atmosphere. Prior work has shown that the high sensitivity of MS instruments can detect the overall changes of organisms’ metabolomes under biotic and nonbiotic stresses. In addition, MS-based metabolomic analyses have been proven to differentiate metabolic signatures between plant genotypes of the same species, , between tree subspecies coexisting in the same environment, and between insects of the same species with different age and sex or even feeding on distinct tree varieties . In addition, MS-based metabolomics techniques have been also applied in aerosol research, i.e., atmospheric-ecometabolomics, and proven to efficiently differentiate chemical fingerprints of ambient samples collected in distinct seasons.…”
Section: Introductionmentioning
confidence: 99%
“…40−42 In addition, MS-based metabolomic analyses have been proven to differentiate metabolic signatures between plant genotypes of the same species, 43,44 between tree subspecies coexisting in the same environment, 45 and between insects of the same species with different age and sex 46 or even feeding on distinct tree varieties. 47 In addition, MS-based metabolomics techniques have been also applied in aerosol research, i.e., atmosphericecometabolomics, 26 and proven to efficiently differentiate chemical fingerprints of ambient samples collected in distinct seasons. Therefore, entire metabolic fingerprints, i.e., a collection of multiple metabolic features detected from samples, can act as unique complex signatures for individual samples that, together with recent bioinformatic methods (i.e., artificial intelligence), can serve to improve tracking of PBAPs.…”
Section: Introductionmentioning
confidence: 99%